Philosophy : The Quest for Truth and Meaning - Beards, Andrew (Book collections on Project MUSE., 2010)
"Philosophy begins, Aristotle said, with wonder; it addresses the great questions of life. This process of self-discovery through philosophy leads one to ask questions not only about human existence but also about God. In Philosophy: The Quest for Truth and Meaning, Andrew Beards introduces readers to some key philosophical ideas - the mind's ability to know truth and reality, metaphysics, ethics, and questioning life's ultimate purpose - in order to guide them in philosophical reflection. By examining the development of philosophy, Beards demonstrates and makes a case for the interplay of faith and reason."--Jacket.